2021
DOI: 10.5194/gmd-14-573-2021
|View full text |Cite
|
Sign up to set email alerts
|

Improving the representation of cropland sites in the Community Land Model (CLM) version 5.0

Abstract: Abstract. The incorporation of a comprehensive crop module in land surface models offers the possibility to study the effect of agricultural land use and land management changes on the terrestrial water, energy, and biogeochemical cycles. It may help to improve the simulation of biogeophysical and biogeochemical processes on regional and global scales in the framework of climate and land use change. In this study, the performance of the crop module of the Community Land Model version 5 (CLM5) was evaluated at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 97 publications
(159 reference statements)
2
37
0
Order By: Relevance
“…Overall, our results indicate an urgent need to bring about a more realistic representation of the seasonal cycles of cropland carbon uptake to prognostic models for better understanding of space‐time patterns in North American carbon fluxes. Recent advances have shown promise in reducing phenology biases through improved mechanistic representation of leaf area index dynamics (Wu et al., 2016), the implementation of active management processes (Lombardozzi et al., 2020), crop‐specific parameterization (Boas et al., 2021; Peng et al., 2018), and/or intensive calibration with flux tower data (Bilionis et al., 2015; Chen et al., 2018). With concerted model development, calibration, and evaluation, the next‐generation of TBMs will undoubtedly be better positioned to deliver more robust estimation of North American carbon fluxes.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, our results indicate an urgent need to bring about a more realistic representation of the seasonal cycles of cropland carbon uptake to prognostic models for better understanding of space‐time patterns in North American carbon fluxes. Recent advances have shown promise in reducing phenology biases through improved mechanistic representation of leaf area index dynamics (Wu et al., 2016), the implementation of active management processes (Lombardozzi et al., 2020), crop‐specific parameterization (Boas et al., 2021; Peng et al., 2018), and/or intensive calibration with flux tower data (Bilionis et al., 2015; Chen et al., 2018). With concerted model development, calibration, and evaluation, the next‐generation of TBMs will undoubtedly be better positioned to deliver more robust estimation of North American carbon fluxes.…”
Section: Resultsmentioning
confidence: 99%
“…6). Low inter-annual variability of yield has also been observed in previous crop simulations with CLM5 for winter wheat (Boas et al, 2021) suggesting that additional drivers of yield variability such as specific management practices are not represented with sufficient detail in CLM5.…”
Section: Biomass Growth and Yieldmentioning
confidence: 84%
“…The stomatal resistance from the Ball‐Berry approach is combined with plant‐specific parameters and atmospheric variables to calculate transpiration. Due to the number of parameters and the difficulty in measuring many of them, the parameters that control transpiration are assumed constant across all vegetation types within the LSMs, even though evidence exists that this is not accurate (Boas et al, 2021; Kattage et al, 2009; Lombardozzi et al, 2020). Due to this limitation, many studies have focused on generic croplands or row crops such as corn and soybean to predict ET in agricultural settings (Lombardozzi et al, 2020; Rajib et al, 2018; Srivastava et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity analyses of the CLM showed that the maximum rate of carboxylation and the Ball‐Berry stomatal resistance slope parameter are the most sensitive parameters that affect simulated ET (Göhler et al, 2013; Yamazaki et al, 2013). More recent efforts have added a crop tool to new versions of CLM (versions 4.5 and 5.0) and parameterized certain row crops using total ET estimated from flux towers, focusing on winter vegetation (Boas et al, 2021; Lu et al, 2017). To our knowledge, vegetation parameterization within CLM has only been done using the total ET , rather than T , which could bias the vegetation‐specific parameterization.…”
Section: Introductionmentioning
confidence: 99%